Apoptosis: a mechanism of cell killing by influenza A and B viruses. - Hinshaw, V S (1994)
In previous studies, we observed that the virulent avian influenza A virus A/Turkey/Ontario/7732/66 (Ty/Ont) induced severe lymphoid depletion in vivo and rapidly killed an avian lymphocyte cell line (RP9) in vitro. In examining the mechanism of cell killing by this virus, we found that Ty/Ont induced fragmentation of the RP9 cellular DNA into a 200-bp ladder and caused ultrastructural changes characteristic of apoptotic cell death by 5 h after infection. We next determined that the ability to induce apoptosis was not unique to Ty/Ont. In fact, a variety of influenza A viruses (avian, equine, swine, and human), as well as human influenza B viruses, induced DNA fragmentation in a permissive mammalian cell line, Madin-Darby canine kidney (MDCK), and this correlated with the development of a cytopathic effect during viral infection. Since the proto-oncogene bcl-2 is a known inhibitor of apoptosis, we transfected MDCK cells with the human bcl-2 gene; these stably transfected cells (MDCKbcl-2) did not undergo DNA fragmentation after virus infection. In addition, cytotoxicity assays at 48 to 72 h after virus infection showed a high level of cell viability for MDCKbcl-2 compared with a markedly lower level of viability for MDCK cells. These studies indicate that influenza A and B viruses induce apoptosis in cell cultures; thus, apoptosis may represent a general mechanism of cell death in hosts infected with influenza viruses.